ChemInform Abstract: Discovery and Development of Natural Product Oridonin‐Inspired Anticancer Agents. Issue 43 (7th October 2016) - Ding, Ye; Ding, Chunyong; Ye, Na; Liu, Zhiqing; Wold, Eric A.; Chen, Haiying; Wild, Christopher; Shen, Qiang; Zhou, Jia
Abstract: Review: 130 refs.